Agentic Subjects and Objects of Political Propaganda: Swedish Media Representations of Children in the Mobilization For Supporting Finland During World War II - Sköld, Johanna; Söderlind, Ingrid (Journal of the history of childhood and youth, 2018)
Children are often portrayed as defenseless victims of war. However, during war periods, issues concerning children's agency are also brought to the fore. Based on media materials describing one country in war (Finland) and relief efforts from a neighbor country (Sweden), this article identifies both Finnish and Swedish children as committed to Finland's cause in different ways. The article shows that children emerge both as agentic subjects and as objects of political propaganda. It argues that children's commitment as represented in the Swedish media could function as propaganda pressuring adults to take action.